Foreign investors’ tendencies and stock market performance in pre- and post-XBRL adoption: evidence from Jordan - Mohammad Mahmoud Humeedat (Cogent Business & Management)
The adaptation of modern technologies to serve economic decision-makers is regarded as an important factor for capital market development. Therefore, this study investigates foreign investors’ tendencies and stock market performance in Pre- and Post-eXtensible Business Reporting Language (XBRL) adoption. Foreign investors’ tendencies were determined by the monthly net foreign investores buying , whereas stock market performance was determined by the monthly market index. Data for 167 listed firms on the Amman Stock Exchange (ASE) were collected for this study during a 6-year period, from 2018 to 2023, including three years before and three years after XBRL adoption. The results of this study show a significant difference in stock market performance but no differences in net foreign investment in pre- and post-XBRL adoption. Multiple regression analysis revealed a strong positive relationship between XBRL adoption and stock market performance and a negative relationship with net foreign investment.